Effect of Glazing on Flexural Strength of Full-Contour Zirconia - Hattanas Kumchai; Patrapan Juntavee; Arthur F. Sun; Dan Nathanson (International Journal of Dentistry)
Objective. The purpose of this study was to evaluate the effect of glazing on flexural strength of highly translucent zirconia materials. Materials and Methods. Specimens of three brands of zirconia bars (Prettau Zirconia, Zirkonzahn; inCoris TZI, Sirona; and Zirlux FC, Pentron Ceramics) were prepared and polished according to manufacturers’ instructions. Final specimen dimensions were 20 × 4 × 2 mm. The specimens from each brand were divided into 3 groups (N = 10): control, heat-treated, and glazed. Heat-treated specimens were fired without the application of the glaze material. The glaze material was applied to the glazed specimens before being fired. A three-point bending test (15 mm span) was performed in an Instron universal testing machine (ISO 6872). Data were analyzed by ANOVA and Tukey’s HSD post hoc test (α = 0.05). Results. Two-way ANOVA showed a significant influence of surface treatments on flexural strength of zirconia materials (P≤0.05). There was no significant difference in flexural strength among the different brands of highly translucent zirconia (P≥0.05). Tukey’s HSD post hoc test showed that specimens in the “glazed” group had significantly lower flexural strength than the control and heat-treated groups (P≤0.05). Conclusion. Within the limitations of the study, external glazing decreased the flexural strength of highly translucent zirconia.